Nerve root sedimentation sign for the diagnosis of lumbar spinal stenosis: reliability, sensitivity, and specificity - Tomkins-Lane, Christy C; Quint, Douglas J; Gabriel, Shaun; Melloh, Markus; Haig, Andrew J (Spine (Philadelphia, Pa. 1976), 2013)
Retrospective review of magnetic resonance images. Examine the diagnostic accuracy, discriminative ability, and reliability of the sedimentation sign in a sample of patients with clinically diagnosed lumbar spinal stenosis (LSS), low back pain (LBP), and vascular claudication, and in asymptomatic controls. The nerve root sedimentation sign (SedSign) was recently described as a new diagnostic test for LSS; however, the degree to which this sign is sensitive and specific in diagnosis of LSS is unknown. All LSS images were obtained from subjects who had clinically diagnosed LSS confirmed on imaging by a spine specialist. The other images were obtained from people with LBP but no LSS, people with severe vascular claudication, and asymptomatic participants. Three blinded raters independently assessed the images. A positive sign was defined as the absence of nerve root sedimentation at the level above or below the level of maximum stenosis. Images from 148 subjects were reviewed (67 LSS, 31 LBP, 4 vascular, and 46 asymptomatic). Intrarater reliability for the sign ranged from κ= 0.87 to 0.97 and inter-rater reliability from 0.62 to 0.69. Sensitivity ranged from 42% to 66%, and specificity ranged from 49% to 78%. Sensitivity improved to a range of 60% to 96% when images with only a smallest cross-sectional area of the dural sac less than 80 mm were included. The sign was able to differentiate (P = 0.004) between LSS and asymptomatic controls but not between LSS and LBP or between LSS and vascular claudication. The SedSign was shown to have high intrarater reliability and acceptable inter-rater reliability. The Sign appears most sensitive in defining severe LSS cases, yet may not aid in the differential diagnosis of LSS from LBP or vascular claudication, or add any specific diagnostic information beyond the traditional history, physical examination, and imaging studies that are standard in LSS diagnosis. 4.